Disinformation as Influencer Marketing Instrument on Social Media - Naufal, Mochammad (Jurnal Indonesia Sosial Sains, 2025)
This research examines how disinformation is used as a marketing tool by influencers on social media. The study employed a qualitative approach with a desk study method, analyzing academic literature, regulatory reports, and viral online news. The results show that disinformation comes in various forms, including exaggerated claims, false testimonials, visual manipulation, and the promotion of illegal investments. These practices have proven effective in attracting audience attention and encouraging interaction, but they cause long-term harm in the form of lost consumer trust, damaged brand reputation, and potential lawsuits. Case studies from 2022–2024 demonstrate the increasing involvement of influencers in investment fraud, illegal sales, and smear campaigns against competing brands. Therefore, it is necessary to emphasize the importance of regulation, digital literacy, and ethical integrity among industry players to maintain the sustainability of digital marketing.